Beyond Forecasting: Using a Modified Delphi Method to Build Upon Participatory Action Research in Developing Principles for a Just and Inclusive Energy Transition. (21st February 2020) - Revez, Alexandra; Dunphy, Niall; Harris, Clodagh; Mullally, Gerard; Lennon, Breffní; Gaffney, Christine
Energy transition debates have been characterized by a strong emphasis on the technical implications of shifting away from fossil fuels to renewable energy sources, with little consideration of social contexts. This is now changing, with a growing emphasis on reconfiguring the social aspects of energy, particularly in terms of introducing more democratic processes into behavior change and energy practice engagements. This article situates itself within these debates and demonstrates the transformative potential of combining participatory action research (PAR) approaches with a modified Delphi method for understanding energy transition issues, particularly beyond forecasting instruments. There remains a dearth in literature combining the Delphi method with PAR; its application in the field of energy transitions is very innovative. PAR draws from grassroots and local-based knowledge, Delphi panels typically focus on the insights from a panel of professional experts. In combining these two approaches, to develop principles for an inclusive and just energy transition, a reflexive form of dialogue emerges that gives voice to what are often considered dissonant or mismatched perspectives. Furthermore, the experimental use of a modified Delphi panel, combined with PAR, offers a strategy to promote knowledge sharing between different groups and to counter potential communication barriers among different actors in society. This article shows how a modified Delphi panel approach is considerably enhanced by combining elements of PAR, raising the potential of Delphi panels beyond forecasting instruments, which often seek to determine the way the future "will be, " toward an envisioning tool that collaboratively seeks to explore the way a low-carbon system "could be, " or perhaps "should be." The development of energy transition principles, endorsed through the modified Delphi panel, offers a concrete way to enact practices of energy justice within a more democratized energy system.